RESOURCE BASED LEARNING (RBL): DAMPAK TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN KOMUNIKASI MATEMATIS - Eka Cahyaningsih; Mujib Mujib; Siska Andriani; Mardiyah mardiyah mardiyah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
Learning model Resource Based Learning exposes students to various learning resources. In addition, students are given the freedom to determine how to complete answers so as to provide opportunities for students to be more skilled in determining answers. The purpose of this study was to determine the critical thinking and mathematical communication skills of students of SMP 2 Pubian Central Lampung. The research method used is the Quasy Experimental Design with Post-test Control Group Design and the sampling technique used in this study is. The homogeneity test uses thetest multivariateof analysis , statistical test research shows that the p-value is smaller than the test criteria (0.000 <0.05) with the significance level of the test criteria, namely 5% or 0.05, in other words it can be concluded that the ability to think critically and Mathematical communication applied with thelearning model Resource Based Learning is better than the critical thinking skills and mathematical communication applied with conventional learning.